Robotic Staging of Cervical Cancer With Simultaneous Detection of Primary Pelvic and Secondary Para-Aortic Sentinel Lymph Nodes: Reproducibility in a First Case Series - Van Trappen, Philippe; De Cuypere, Eveline; Claes, Nele; Roels, Sarah (Frontiers in Surgery, 2022)
Objective: Currently, surgical staging of locally advanced cervical cancer and cervical cancer with suspicious lymph nodes on imaging includes a complete para-aortic lymph node dissection. In this study we aim to assess the reproducibility of our recently reported robotic technique, using indocyanine green, for identifying simultaneously primary pelvic and secondary para-aortic sentinel lymph nodes (SLNs) in a first case cohort of cervical cancer patients. Methods: A retrospective case series of cervical cancer patients with locally advanced cervical cancer and/or suspicious lymph nodes (LNs) on imaging. All patients underwent a robotic pelvic SLN and para-aortic sentinel/non-sentinel LN dissection using the da Vinci Xi platform. Indocyanine green was used as fluorescent tracer, at a concentration of 1.9 mg/ml, and injected as 0.5ml in each quadrant of the cervix. Results: In a total of 10 cases, primary pelvic SLNs (90% bilateral) with subsequent secondary para-aortic SLNs were identified in all cases. Lower para-aortic SLNs were present in all cases, upper para-aortic SLNs were found in 9 out of 10 cases. The mean age of the cervical cancer patients was 49.8 years (SD +/- 6.89) and the mean BMI (kg/m2) was 23.96 (SD +/- 4.60). The median total operative time was 105.5 minutes (range, 89-141 min). The mean number of primary pelvic SLNs, secondary lower and upper para-aortic SLNs was 3.10 (SD +/- 1.10), 2.90 (SD +/- 0.74) and 2.30 (SD +/- 1.57) respectively. The median number of total PALNs dissected per patient was 11.5. Six patients had positive primary pelvic SLNs, and two had secondary positive para-aortic SLNs. The non-sentinel para-aortic LNs were negative in all cases. There were no intra- or postoperative complications. Conclusion: Our preliminary experience demonstrates the reproducibility of identifying, besides primary pelvic SLNs, secondary lower and upper para-aortic SLNs during robotic staging in cervical cancer. A surgical approach limiting a complete para-aortic LN dissection could reduce the potential risks and morbidity associated with this procedure. To establish the sensitivity and negative predictive value of this new surgical approach large prospective observational studies are needed.